1998
DOI: 10.1017/s0007114598001305
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of non-starch polysaccharides in mixed diets and single fibre sources: comparative studies in human subjects andin vitro

Abstract: The present study investigated whether the extent of fermentation of NSP in human subjects could be predicted by an in vitro batch system. Fibre sources studied were five mixed diets containing different amounts and types of fibre and three single fibre sources (citrus fibre concentrate, coarse and fine wholemeal rye bread). Fermentation in human subjects was determined in balance experiments in women who were also donors of the faecal inocula. In vitro fermentations were performed with fibre residues prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…In addition, in vitro fermentation for 24 h was sufficient to mimic the polysaccharide degradation in vivo (Wisker, Daniel, Rave, & Feldheim, 1998). In the present work the TPC determined in the extracts following in vitro colonic fermentation for 24 h ranged from 4.5 to 17.1 FAE/g of cooked grain (dw).…”
Section: 2mentioning
confidence: 64%
“…In addition, in vitro fermentation for 24 h was sufficient to mimic the polysaccharide degradation in vivo (Wisker, Daniel, Rave, & Feldheim, 1998). In the present work the TPC determined in the extracts following in vitro colonic fermentation for 24 h ranged from 4.5 to 17.1 FAE/g of cooked grain (dw).…”
Section: 2mentioning
confidence: 64%
“…Short-chain fatty acid concentration in feces is a reasonable measurement of colonic fermentability. However, model intestinal fermentation is a more rapid, non-invasive, method of assessing fermentability and results from this method correspond with fermentability in vivo [27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…In vitro fermentation methods are a representative model of colonic fermentation, and work well to predict substrate availability and ability for fermentation in the gut [12]. Previous preliminary studies have shown that WD and PHGG ferment in the large intestine producing measurable levels of beneficial Bifidobacteria and Lactobacillus at 24 h, indicating that both dietary fibers demonstrate a prebiotic effect [13].…”
Section: Introductionmentioning
confidence: 99%